Apuntes sobre dos modos de ver telenovelas - Sonia Muñoz (Estudios sobre las Culturas Contemporáneas)
The article provides a tought-provoking comparative analysis of the "ways of watching" soap operas between adult women from popular neighborhoods and young middle-class students in Cali, Colombia. An understanding of the different logistics underlying the singular cultural appropriation of soap operas is attemp)- ted.